Little Steamship on the Prairie: Grass-Roots Preservation and Artistic Interpretation in the Construction of Ethnic, Local, and National Identities - DuBois, Thomas A. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2023)
The enigmatic life of Finnish-Canadian pioneer Tom (Damianus) Sukanen (1878-1943) is discussed in connection with his steamship Sontiainen, today preserved at the Sukanen Ship Pioneer Village and Museum, outside of Moose Jaw, Saskatchewan. The article examines details of Sukanen's life and the wide array of plays, novels, films, and musicals that have been made about him since the 1970s. The question of representing heritage through preserved artifacts and museums is explored.